Microglia: An Active Player in the Regulation of Synaptic Activity - Kyungmin Ji; Jeremy Miyauchi; Stella E. Tsirka (Neural Plasticity)
Synaptic plasticity is critical for elaboration and adaptation in the developing and developed brain. It is well established that astrocytes play an important role in the maintenance of what has been dubbed “the tripartite synapse”. Increasing evidence shows that a fourth cell type, microglia, is critical to this maintenance as well. Microglia are the resident macrophages of the central nervous system (CNS). Because of their well-characterized inflammatory functions, research has primarily focused on their innate immune properties. The role of microglia in the maintenance of synapses in development and in homeostasis is not as well defined. A number of significant findings have shed light on the critical role of microglia at the synapse. It is becoming increasingly clear that microglia play a seminal role in proper synaptic development and elimination.